CRITICAL DISCOURSE ANALYSIS OF VAN DIJK ON VOI NEWS OF FORMULA E “JAKARTA E-PRIX” IN POLITICAL ISSUES - Irmayani; Rahmi Usman (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
This research aimed to explain about hot the news was constructed by reporter and also how media institution ideology and the narration an issue spread to public affect to the characteristic of certain news. The object of the research was five news about Formula E posted by online news portal, VOI where the tittles were: “A Condition That Must Be Fulfilled By Formula E If You Want To Get Support From PDIP,” “Sahroni Sindir No BUMN Sponsors Formula E: Sorry, BUMN Is Part Of The Republic Of Indonesia, Right?,” “Erick Thohir Reluctant to Comment on BUMN Not Sponsoring Formula E, Arya Sinulingga Gives Comprehensive Explanation,“ “Anies Baswedan: Formula E Has No Handlers!,” and ”Formula E Tickets Sold Out Ahmad Sahroni, Denny Siregar: There Must Be Saved Faces to be Nominated In 2024.” This research used critical discourse analysis in analyzing the texts through using Van Dijk’s theory. Van Dijk’s model focused on the text, social cognition and social context analysis. The result revealed that most of VOI news about Formula E is presented in political perspective and in presenting the news about Formula E, despite of had dynamic characteristic in particular perspective either the central government who represented by BUMN or Formula E committee and Anies Baswedan as Governor of DKI Jakarta, but VOI tend to bias in presenting particular person and group.